Análisis biométrico del caballo Criollo Araucano (2017)
This research is focused on determining the relationships of body traits in Araucano Criollo Horse. For this purpose, a principal component analysis was carried out on 52 adult males, in which the studied body characters were the following 20: chest circumference, longitudinal diameter, back-sternal diameter, height at the withers, transverse chest width, height of the substernal bone, chest width, perimeter of the anterior cannon, head length, head width, skull length, skull width, face length, face width, head depth, height at the rump, rump length, rump width, height to the birth of the tail and up to the hock. Possible morphological differences from four Araucan farms were also analyzed. It can be concluded that this local horse, though fairly uniform, presents morphological differences depending on the area that the animals come from and these differences lay in the overall appearance rather than focus on specific body regions. © 2017, Universidad de Cordoba,Servicio de Publicaciones. All rights reserved.